Pengaruh Literasi Keuangan dan Kepercayaan Terhadap Minat Investasi Digital Mahasiswa - Christina Adelia; Endah Dewi Purnamasari; Emilda Emilda (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2026)
The increasing accessibility of digital investment among university students has not been fully accompanied by a high level of investment interest. This study aims to analyze the effect of financial literacy and trust on students’ interest in digital investment in Palembang City. This research employs a quantitative approach with a sample of 400 students, and the data are analyzed using SPSS version 26. The results show that financial literacy and trust have a positive and significant effect on digital investment interest. Financial literacy has a t-value of 6.540 with a significance level of 0.000 (<0.05), indicating a strong influence, while trust also demonstrates a significant effect with a significance level of less than 0.05. These findings indicate that higher financial literacy enhances students’ understanding of investment instruments, risks, and returns, while greater trust in the security, transparency, and credibility of digital platforms increases their willingness to invest. The implications of this study highlight the importance of strengthening financial literacy education in higher education institutions and improving the security and transparency of digital platforms to build student trust. Therefore, a combination of strong financial literacy and trust can foster more rational and responsible digital investment behavior among young generations.